Optimum Research of Planar 5R Symmetric Parallel Robot based on the Performance Indicator about GTW and GTI - Zeqi Wu; Jing He; Zhijun Wang; Liantao Du (Jixie chuandong)
Optimum design about geometric parameters，i.e. link lengths is one of the most important issues in the field of parallel robots. In order to facilitate optimization of the geometric parameters of 5R parallel robot，the following steps are given. First，the planar design spaces of the 5R symmetric parallel robot are drawn. Then，using the concept of transmission angle，the good transmission workspace （GTW） and global transmission index （GTI） are defined by reasonable range of LTI（Local Transmission Index）. The GTW and GTI atlas are given in the planar design space. Finally，the optimization design process is given，and the optimum design of planar 5R symmetric parallel manipulator is conducted based on the performance atlases. As long as the transmission angle is kept within a certain range，the optimized robot not only can meet the needs of work，but also has excellent performance on motion and force transmission.